-7(3x-7)-6=239-7

Simple and best practice solution for -7(3x-7)-6=239-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(3x-7)-6=239-7 equation:



-7(3x-7)-6=239-7
We move all terms to the left:
-7(3x-7)-6-(239-7)=0
We add all the numbers together, and all the variables
-7(3x-7)-6-232=0
We add all the numbers together, and all the variables
-7(3x-7)-238=0
We multiply parentheses
-21x+49-238=0
We add all the numbers together, and all the variables
-21x-189=0
We move all terms containing x to the left, all other terms to the right
-21x=189
x=189/-21
x=-9

See similar equations:

| 101=6v+5 | | (2x-5)=(4x-25) | | 12.02=0.6h | | -7v-4v=-11 | | 2x^2+8x=72 | | y/5+16=34 | | -6x=-8-2x | | d/19+6=7 | | x+40°=180° | | 4x+12-3x=38 | | 3a-16=32 | | 16=-2+3b | | x2-5/2=15 | | x+68+2x-68=180 | | 2=x/3+6 | | ÷3(10+2x)=4 | | 2x+21=31 | | x+68=2x-68=180 | | 249=0.04x+9 | | (10+2x)÷3=4 | | x+3+6=16 | | 3x^2-16=180 | | 5x+3(2x-3)=9x-5+2x | | 4x-7-2x=5 | | x+2x+4x=7x= | | x-22=2x-60 | | x3+3x2-5x-15=0 | | 11x-48=7x | | 3x-42=5x-100 | | x+2x+4x=7x=14 | | 9(w-9)-2=-7+7(w-8 | | 9x+8-12=3x+2 |

Equations solver categories